The Influence of Taxpayer Awareness, Fiscus Services, Tax Sanctions, Taxation System and Tax Socialization on Individual Taxpayer Compliance at KPP Pratama Medan Polonia - Siti Alsyukroni; Ina Liswanty (Jurnal Manajemen Bisnis Eka Prasetya, 2023)
This research was conducted with the aim of determining the influence of taxpayer awareness, tax authorities services, tax sanctions, tax systems and tax socialization on individual taxpayer compliance at KPP Pratama Medan Polonia using quantitative research methods with primary and secondary data sources. through a questionnaire with five Likert scales. The respondents in this research were 100 Taxpayers with total sampling. Data processing in this study used SPSS 25.0. The results of this research indicate that Taxpayer Awareness, Fiscus Service, Tax Sanctions have an influence on Individual Taxpayer Compliance, while the Tax System and Tax Socialization have no influence on Individual Taxpayer Compliance. The R Square value of the variables studied is 0.314, there is a remaining 0.686 which has not been studied.